2015
DOI: 10.1200/jco.2014.60.3217
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in a Randomized Phase III Study of Bevacizumab, Temozolomide, and Radiotherapy in Newly Diagnosed Glioblastoma

Abstract: The addition of bevacizumab to standard-of-care treatment for newly diagnosed glioblastoma had no impact on HRQoL during the progression-free period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 31 publications
3
55
0
1
Order By: Relevance
“…BEV was found to prolong PFS in newly diagnosed GBM patients, but not to significantly improve QoL during this period. 19 Certain patient subpopulations with HGG recurrences may, nonetheless, benefit from BEV by stabilizing the patients' condition. Moreover, several phase II and III trials with novel targeted agents have been conducted over the last few years; however, these studies were mainly single-center trials with limited numbers of patients as well as ambiguous results, and a real breakthrough is still to be desired.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…BEV was found to prolong PFS in newly diagnosed GBM patients, but not to significantly improve QoL during this period. 19 Certain patient subpopulations with HGG recurrences may, nonetheless, benefit from BEV by stabilizing the patients' condition. Moreover, several phase II and III trials with novel targeted agents have been conducted over the last few years; however, these studies were mainly single-center trials with limited numbers of patients as well as ambiguous results, and a real breakthrough is still to be desired.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…However, HRQoL outcomes differed. 66,67 The AVAglio study showed that the addition of bevacizumab neither worsened nor improved HRQoL (EORTC QLQ-C30 and QLQ-BN20; global health, physical functioning, social functioning, motor functioning, and communication deficit) over time. 66 Time to HRQoL deterioration was longer in the bevacizumab arm, which is in line with prolonged progression-free survival.…”
Section: Newly Diagnosed Glioblastomamentioning
confidence: 99%
“…66,67 The AVAglio study showed that the addition of bevacizumab neither worsened nor improved HRQoL (EORTC QLQ-C30 and QLQ-BN20; global health, physical functioning, social functioning, motor functioning, and communication deficit) over time. 66 Time to HRQoL deterioration was longer in the bevacizumab arm, which is in line with prolonged progression-free survival. It can be concluded from this study that the addition of bevacizumab resulted in an increased progressionfree survival in combination with a delay in HRQoL deterioration, which may be a meaningful outcome for patients.…”
Section: Newly Diagnosed Glioblastomamentioning
confidence: 99%
“…The AVAglio group recently reported its health-related quality of life (HRQoL) data in full, but were unable to conclude whether bevacizumab has a net clinical benefit in patients with newly diagnosed glioblastoma. 1 Their observations suggested that a deterioration in HRQoL is mainly driven by disease progression rather than treatment. Furthermore, an economic assessment published alongside the AVAglio report concludes that use of bevacizumab at this stage of the disease is probably not cost-effective.…”
mentioning
confidence: 98%